About new approaches to the solution of heat problem of chilling of 3D objects - A. N. Chichko; A. S. Borozdin (Литьë и металлургия)
In this article there is examined one of the actual problems of the mathematical modelling of thermal processes ~ optimization of numerical solution of the thermal conduction equation. The dynamic increase of similarity groups using the new method is reflected.